The Sustainability Status of Vannamei Shrimp (Litopenaeus vannamei) Aquaculture in Millennial Pond Model: Sustainability Status of Vannamei Shrimp (Litopenaeus vannamei) Aquaculture in Millennial Pond Model - Arif, Gunarso; Prayitno, Slamet Budi; Purnomo, Pujiono Wahyu (Department of Aquaculture, 2025)
Vannamei shrimp (Litopenaeus vannamei) aquaculture activities in Jepara Regency are conducted at Brackish Water Aquaculture Centers (Balai Besar Perikanan Budidaya Air Payau/BBPBAP) Jepara with a millennial model. This aquaculture model features a critical point in the middle of the pond, which aims to reduce the risk of failure due to pathogenic virus attacks. However, in running a vannamei shrimp aquaculture, an appropriate strategy is required for business development and sustainability. In this study, a multidimensional scaling (MDS) method was used to analyze the ecological, economic, social, technological, and legal-institutional dimensions. The study was conducted during October-December 2024, in which primary data collection was carried out through interviews with respondents and secondary data from related data references. The results of the study showed that the sustainability values were 88.39 (ecological dimension), 81.05 (economic dimension), 75.25 (social dimension), 99.996 (technological dimension), and 99.996 (legal-institutional dimension). The average value of the sustainability index of vannamei shrimp farming in the millennial pond of BBPBAP Jepara was very sustainable, with a score of 88.94. Based on the leverage analysis, sensitive attributes obtained in this study were ecological domain (1) disease attacks (2) land utilization level (3) land suitability, economic domain (1) price trends, (2) market reach, (3) cultivation profits, social domain (1) education level, (2) community involvement/labor absorption, (3) availability of transportation and communication facilities, technology domain (1) pond construction (2) application of biosecurity and legal domain & (1) institutional training activities and socialization about cultivation businesses (2) availability of cultivator groups.